Determinant of cultural heritage on the spatial setting of cultural landscape: a case study on the northern region of Thailand - Junjira Nunta; Nopadon Sahachaisaeree (My University, 2010)
The research aims to investigate the spatial organization of landscape vis-à-vis the functional-behavioral settings of the local residence. Beliefs and social structure are analyzed vis-à-vis the development of physical conditions. Finally, the research examines dwellers' perceptual response to the dynamic of cultural landscape. The research indicates that cultural landscape and physical area affect the perception and response of dwellers. Cultural identities are highly associated with the dynamic of cultural landscape. Spatial settings of newly developed urban areas should taking into consideration the local livelihood and residents' inherited pattern of believe and ritual practice reflected upon the planned cultural landscape.
Keywords: Cultural landscape; Affect; Architectural and Urban Studies